Simulation education in the internet age: some experiences on the use of pure online and blended learning models - Fonseca, Pau; Juan, Angel A.; Pla, Lluis M.; Rodriguez, Sara V.; Faulin, Javier (Winter Simulation Conference, 2009)
In this paper we analyze several cases related to three different Spanish universities that make use of the World Wide Web to teach simulation courses online. These universities are the Open University of Catalonia, the University of Lleida and the Public University of Navarre. At these three universities different infrastructures, tools and learning models are employed to deliver simulation education online. All together, they represent a good example of how information technologies can be used in today's higher-education systems and, in particular, in the area of simulation education. In the paper, several course designs are covered and main difficulties associated with these online courses are highlighted and discussed. Intensive use of computer simulation software, collaborative e-learning practices and professional-oriented approaches are proposed as methodological policies to increase students' motivation for simulation topics.